When rights collide with reality : an argument for dialogic approach by the African court on Human and Peoples' Rights to the 'effective remedy' principle based on a distributive justice Ethos - Mbazira, Christopher (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.